Empowering Madagascan women with environmental know-how - Ann-Kathrin Zotz (International Trade Forum, 2016)
It is somewhat ironic that with more than 3 billion people, the rural poor, who have very little in the way of personal resources, constitute the largest group of natural resource managers. Within this group, women have a key role in sourcing natural resources as farmers and household providers. They are responsible for harvesting, collecting of fuel and water and cultivating subsistence crops.